An assessment of wind turbine characteristics and wind energy characteristics for electricity production - Akpinar, E. Kavak; Akpinar, S. (Taylor & Francis Inc, 2006)
This work is an analysis of wind turbine characteristics and wind energy characteristics of four regions around Elazig, Turkey, namely Maden, Agin Elazig and Keban. Wind speed data and wind direction in measured hourly time-series format is statistically analyzed based on 6 years between 1998 and 2003. The probability density distributions are derived from time-series data and distributional parameters are identified. Two probability density functions are fitted to the measured probability distributions. The wind energy characteristic of all the regions is studied based on the Weibull and the Rayleigh distributions. Using the Weibull probability density function, we estimated the wind energy output and the capacity factor for six different wind turbines between 300 and 2300 kW during the six years. It was found that Maden is the best region, among the regions analyzed, for wind energy characteristic and wind turbine characteristic.
Keywords: Weibull and Rayleigh distributions; wind energy; wind turbines